The moderating effect of imagery ability on perceived vividness: the case of HPV vaccine advertising in China - Yang, Fan; Guo, Steve (Chinese journal of communication, 2015)
This research investigates the effects of the relationship between imagery ability and pictorial appeal on vividness perception, free recall, and attitude. To investigate the potential effects of HPV vaccine advertising in mainland China, we conducted an experiment using a sample of 147 college female students who were randomly assigned to treatment and control groups. The results of the analyses showed that pictorial appeal and imagery ability exerts a joint impact on vividness perception, recall, and attitude. The subjects with high-imagery ability perceived more vividness when pictorial appeal was absent, whereas the cognitive performance of the subjects with low-imagery ability was mainly enhanced by pictorial presence. We found that whether a message was perceived as vivid or not was more a function of imagery ability than an attribute of the message. In addition, the findings indicated that vividness perception mediated this moderating effect. The implications for health communication theory and education are discussed.